Observations of the solar UV irradiance and ozone column at Svalbard - Petkov, BH; Vitale, V; Hansen, GH; Svendby, TM; Sobolewski, PS; Láska, K; Elster, J; Viola, A; Mazzola, M; Lupi, A (Zenodo, 2019)
This is chapter 8 of the State of Environmental Science in Svalbard (SESS) report 2018 (https://sios-svalbard.org/SESS_Issue1). Solar radiation is the earth’s main energy source and governs a variety of chemical and biological processes in the atmosphere and biosphere. The amount of solar radiation that enters the atmosphere varies mainly due to two important astronomical parameters. First, Earth’s orbit is elliptical rather than perfectly round; second, the planet’s spin axis is tilted in relation to the plane of its orbit. These parameters cause seasonal changes at different latitudes and polar nights and days. As it passes through the atmosphere, solar radiation is scattered and absorbed by molecules and aerosols. Scattering and absorption are complex processes that strongly depend on a range atmospheric parameters and conditions, and they induce additional variations in the amount of solar radiation that reaches the earth’s surface. Thus, examination of the variability in the irradiance at the surface can contribute significantly to our knowledge about atmosphere and climate. Solar ultraviolet (UV) radiation reaching Earth’s surface is an important factor for various chemical and biological processes. Propagating through the atmosphere, a significant part of UV irradiance is strongly absorbed by atmospheric ozone, which in turn raises the temperature of the middle atmosphere and affects dynamical processes. This makes the study of solar UV radiation and the total amount of ozone an important task. At Svalbard, measurement UV radiation and ozone levels started in 1950 and continue to this day. This long observational series has provided better understanding of the climatic processes in polar regions, and the conclusions reached through these years have been published in scientific journals. However, our picture of the polar environment is still far from complete.